IMPLEMENTATION OF LORA WITH TEMPERATURE SENSORS IN IRRIGATION AREA (CASE STUDY: MARTAPURA CITY) - Muhammad Mirza Hafiz Yudianto; Dodon Turianto Nugrahadi; Dwi Kartini; M. Itqan Mazdadi; Friska Abadi (Journal of Data Science and Software Engineering, 2022)
This study applies to the concept of a Wireless Sensor Network (WSN) consisting of a transmitting instrument and a receiving instrument using Long Range (LoRa) data transmission with a frequency of 915 MHz and LoRa 920 MHz. The test is divided into 2 tropical weather conditions, namely when the weather is sunny and rainy. The test results show that the maximum distance that the LoRa transmitter can reach is 1 kilometer. The QoS (Quality of Service) parameters used to consist of Delay, Throughput, RSSI, & SNR. Based on the test results of the QoS parameters, both frequencies affect tropical weather conditions and increase as the distance of data collection increases. LoRa Frequency 915 MHz and Frequency 920 MHz have their respective differences and advantages, which are uncertain on weather conditions and data transmission distances.